2003
DOI: 10.1177/00187267030568005
|View full text |Cite
|
Sign up to set email alerts
|

When a Leader Dies

Abstract: The reactions of followers after losing a leader are an important and neglected area of study. In fact, little is known about reactions to changes of leadership in organizational settings, generally. The effects of loss and specifically of bereavement within the family are well known. Whilst organizational life differs from family life, some relationships and reactions to loss may be comparable. One way of illuminating reactions to the loss of a leader is to look empirically at cases of leadership loss. This a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
1
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 14 publications
0
25
1
1
Order By: Relevance
“…Buffering or protecting participants from change anxiety was identified in the literature as one approach taken by change agents (Hyde & Thomas , Baruch & Lambert , Stefancyk et al . ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Buffering or protecting participants from change anxiety was identified in the literature as one approach taken by change agents (Hyde & Thomas , Baruch & Lambert , Stefancyk et al . ).…”
Section: Discussionmentioning
confidence: 99%
“…() reported on a study in which they hypothesised that it was the relationship between the change agent and participants that influenced the change process; they suggested that by reducing uncertainty about the anticipated change, this reduced the participants’ negative expectations about the change, which resulted in a higher level of participants’ commitment to the ongoing change process. Both Baruch and Lambert () and Hyde and Thomas () suggest that effective change agents, or leaders absorb the anxiety experienced by the organisation as part of their function.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Humphrey, Zimpfer, 2007;Worden, 2009). Ce paradigme dominant s'inscrit en résonance avec ce que Walter (1994) Albert (1984); Kets de Vries, Miller (1985); Sutton (1987); Kets de Vries, Balazs (1996,1997); Cunningham (1997); Roy (1997); Pailot (1999Pailot ( , 2000; Marks, Mirvis (2001); Dubouloy, Fabre, (2002); Hyde, Thomas (2003); Zell (2003); Brewington, Nassar-MacMillan, Flowers, Furr (2004); Blau, (2006Blau, ( , 2007; Malarewicz (2006Malarewicz ( , 2011; Dubouloy (2005Dubouloy ( , 2008; Bah (2009Bah ( , 2009 (Mazade, 2011). La plupart de travaux sur les parcours biographiques opère une distinction entre les transitions (moments de passages prévisibles) et les bifurcations biographiques (situations provoquées par la survenue d'événements partiellement imprévisibles) (voir Bidart, 2006;Grossetti, 2006;Hélardot, 2006;Bessin, Bidart, Grossetti, 2010).…”
Section: Les Usages De Deuil Dans Les Sciences Organisationnellesunclassified
“…However, some important topics and questions remain unaddressed in this special issue. A significant aspect of the study of organizational death involves understanding how people respond to the death of individuals, such as through the impact of the death of a leader on an organizational culture (Hyde and Thomas 2003), the death of employees in work-related suicides (Seignour and Palpacuer 2010) or fatal accidents at work (Slapper 1999). Although John Cullen's article in this special issue deals with the important issue of suicide in relation to employment, there are numerous other ways in which organizations provide the context in which individual death occurs and contribute towards causing the death of individuals, such as by requiring them to work excessively long hours or in dangerous conditions.…”
Section: The Future Of Organizational Deathmentioning
confidence: 99%